2010
DOI: 10.3109/13561820.2010.532620
|View full text |Cite
|
Sign up to set email alerts
|

Development and pilot testing of the collaborative practice assessment tool

Abstract: Collaborative practice is receiving increased attention as a model of healthcare delivery that positively influences the effectiveness and efficiency of patient care while improving the work environment of healthcare providers. The collaborative practice assessment tool (CPAT) was developed from the literature to enable interprofessional teams to assess their collaborative practice. The CPAT survey included 56 items across nine domains including: mission and goals; relationships; leadership; role responsibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 26 publications
0
82
0
4
Order By: Relevance
“…1,18 Before IPP can successfully occur in the workforce, health care practitioners must learn interprofessionally. These IPE experiences can occur precertification or postcertification as part of the CEUs many health care professions require to maintain certification.…”
Section: Discussionmentioning
confidence: 99%
“…1,18 Before IPP can successfully occur in the workforce, health care practitioners must learn interprofessionally. These IPE experiences can occur precertification or postcertification as part of the CEUs many health care professions require to maintain certification.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that interprofessional collaboration in practice may improve patient care and outcomes, reduce medical errors, and enhance job satisfaction and retention. 29 Therefore, the next generation of health professionals must be prepared to successfully function in this culture. Various entities have suggested that the preparation of the health care workforce should include IPE, 24,30 and have identified health care competencies for all health care providers, regardless of discipline.…”
Section: Postprofessionalmentioning
confidence: 99%
“…Opie (1997Opie ( , 2000 calls this discursive knowledge work, 1 and communication can be considered the interprofessional practice itself. One of this article's main contributions is its suggestion that the interprofessional patient case review-as communicative practice-should serve as a site for inquiry into ICP, as it is here that shared mental models, shared goals, and role and situation awareness are brought to life (Atwal & Caldwell, 2006;Billett, 2014;Evans & Baker, 2012;San Martín-Rodríguez, Beaulieu, D' Amour, & FerradaVidela, 2005;Schroder et al, 2011;Suter et al, 2009 Communication.…”
Section: Implications For Interprofessional Practicementioning
confidence: 99%